Dampak transaksi non tunai terhadap perputaran uang di Indonesia - Zakhariantara Gintting; Syaipan Djambak; Mukhlis Mukhlis (Jurnal Ekonomi Pembangunan, 2018)
The objective of this study was to analyze the impact of the use of electronic money (e-money) to the velocity of money in Indonesia. The use of this payment instrument makes consumers easy to pay, thereby increasing the level of consumption. Data used is the nominal of transaction in 2013 to 2017 from Bank Indonesia database. The method in this study used regression model with OLS (Ordinary Least Square) estimate. The finding in this study showed e-money transactions consisting of the nominal e-money transactions, nominal ATM-Debit card transactions and nominal credit card transactions partially no significant effect on the velocity of money in Indonesia